Grain Growth and Yield of Wheat as Influenced by Variety and Sowing Date (Bangladesh Agronomy Journal, 2016)
A field experiment was conducted at the Agronomy field, Sher-e-Bangla Agricultural University, Dhaka during November 2012 to April 2013 to evaluate the influence of variety and sowing date on grain growth and yield of wheat. The experiment consisted of four wheat variety viz., BARI Gom-21, BARI Gom-24, BARI Gom-25 and BARI Gom-26 and three sowing date viz., 20 November, 01December and 12 December. Grain growth, yield contributing characters and yield of wheat were significantly influenced by different variety and sowing date. Among the variety, BARI Gom-24 and BARI Gom-25 showed initial lower lag phase duration of 8 days after anthesis (DAA) and 12 DAA, respectively than BARI Gom-21 (16 DAA) sown at 01 December. The maximum grain growth rate whole over the period was maintained by BARI Gom-26 sown at 01 December. It reached peak at 20 DAA (1.17 mg /grain/day). The minimum growth rate was maintained by BARI Gom-21 and BARI Gom-24 sown at 12 December (0.15 mg /grain/day). BARI Gom-25 sown at 01December gave the highest yield (4.6 t ha?1) whereas BARI Gom-21 sown at 20 November gave the lowest (2.67 t ha?1). All the wheat varieties sown at 01 December yielded better than 20 November and 12 December sowing.Bangladesh Agron. J. 2015, 18(2): 97-104